The Adria Microplate: GPS Geodesy, Tectonics and Hazards - Pinter, Nicholas; Grenerczy, Gyula; Weber, John.; Stein, Seth.; Medak, Damir; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
Tectonic motion of the Adria microplate exerts a first-order control on the tectonics, geology, seismology, resource distribution, and the geological hazards across a broad zone of south-central Europe and the north-central Mediterranean. Since its first application to geodynamical problems, GPS geodesy has gradually revealed the nature of motion and deformation for most active areas of deformation across the Earth. One of the last remaining regional-scale problems on the planet is the motion and associated deformation in the peri-Adriatic region. Selected local-scale studies have examined aspects of this motion, but to date no truly regional analysis or regional team has systematically attacked the full breadth of this problem. A NATO Advanced Research Workshop (ARW) was held in Veszprém, Hungary from April 4-7, 2004. This workshop brought together a distinguished international group of scientists working in the peri-Adriatic region to: (1) review research activities and results, (2) share technical expertise, and (3) provide a springboard for future collaborative research on Adria geodynamics. Areas of agreement were identified, as well as remaining areas of debate. In addition, attention focused on important scientific questions and the potential for international and interdisciplinary research in the future.
RECENT ADVANCES IN PERI-ADRIATIC GEODYNAMICS AND FUTURE RESEARCH DIRECTIONS -- PLEISTOCENE CHANGE FROM CONVERGENCE TO EXTENSION IN THE APENNINES AS A CONSEQUENCE OF ADRIA MICROPLATE MOTION -- PLATE TECTONIC FRAMEWORK AND GPSDERIVED STRAIN-RATE FIELD WITHIN THE BOUNDARY ZONES OF THE EURASIAN AND AFRICAN PLATES -- POST-LATE MIOCENE KINEMATICS OF THE ADRIA MICROPLATE: INFERENCES FROM GEOLOGICAL, GEOPHYSICAL AND GEODETIC DATA -- PALEOMAGNETIC EVIDENCE FOR TERTIARY COUNTERCLOCKWISE ROTATION OF ADRIA WITH RESPECT TO AFRICA -- PALEOMAGNETIC CONSTRAINTS FOR THE RECONSTRUCTION OF THE GEODYNAMIC EVOLUTION OF THE APENNINES DURING THE MIDDLE MIOCENE - PLEISTOCENE -- GEO-STRUCTURAL EVIDENCE FOR ACTIVE OBLIQUE EXTENSION IN SOUTH-CENTRAL ITALY -- RATES OF LATE NEOGENE DEFORMATION ALONG THE SOUTHWESTERN MARGIN OF ADRIA, SOUTHERN APENNINES OROGEN, ITALY -- THE ALBANIAN OROGEN: CONVERGENCE ZONE BETWEEN EURASIA AND THE ADRIA MICROPLATE -- LATE CENOZOIC TECTONICS OF SLOVENIA: STRUCTURAL STYLES AT THE NORTHEASTERN CORNER OF THE ADRIATIC MICROPLATE -- RECENT MONITORING OF CRUSTAL MOVEMENTS IN THE EASTERN MEDITERRANEAN The Use of GPS Measurements -- CONSORTIUM FOR CENTRAL EUROPEAN GPS GEODYNAMIC REFERENCE NETWORK (CEGRN CONSORTIUM) -- GEODYNAMIC INVESTIGATION IN BOSNIA AND HERZEGOVINA -- INSTRUMENTATION FOR TERRESTRIAL MEASUREMENTS OF GEODYNAMICS AND THE MAIN SOURCES OF DISTURBANCE -- VERTICAL MOVEMENTS IN SLOVENIA FROM LEVELING DATA -- GEOID DETERMINATION IN SERBIA -- PROCESSING OF GEODYNAMIC GPS NETWORKS IN CROATIA WITH GAMIT SOFTWARE -- ACTIVE DEFORMATION OF THE NORTHERN ADRIATIC REGION:Results from the CRODYN geodynamical experiment -- FRAGMENTATION OF ADRIA AND ACTIVE DECOLLEMENT TECTONICS WITHIN THE SOUTHERN PERI-TYRRHENIAN OROGEN, ITALY -- GEODETIC MEASUREMENTS IN THE AEGEAN SEA REGION FOR THE DETECTION OF CRUSTAL DEFORMATION -- THE PIVO-2003 EXPERIMENT: A GPS STUDY OF ISTRIA PENINSULA AND ADRIA MICROPLATE MOTION, AND ACTIVE TECTONICS IN SLOVENIA -- CRUSTAL DEFORMATION BETWEEN ADRIA AND THE EUROPEAN PLATFORM FROM SPACE GEODESY -- SEISMICITY ALONG THE NORTHWESTERN EDGE OF THE ADRIA MICROPLATE -- SEISMICITY OF THE ADRIATIC MICROPLATE AND A POSSILE TRIGGERING: GEODYNAMIC IMPLICATION -- SEISMIC HAZARD IN THE PANNONIAN REGION -- SOCIETAL ASPECTS OF ONGOING DEFORMATION IN THE PANNONIAN REGION.
Keywords: Geophysics; Structural geology; Geology; Geotechnical engineering; Geochemistry; Geophysics/Geodesy.; Structural Geology; Geology; Geotechnical Engineering & Applied Earth Sciences; Geochemistry